Sistem Informasi Presensi Personil Pada Polsek VII Koto - Yuhana Widiatmiko, Ika; Zaenal Abidin, Dodo (LPPM Universitas Dinamika Bangsa, 2024)
The recording and reporting of personnel attendance at Polsek VII Koto are highly crucial in maintaining discipline among Civil Servants within the Indonesian National Police (Polri). Presently, attendance recording is still done manually in attendance books. The compilation of attendance is carried out using a Microsoft Excel application, which can lead to data errors, damages, and even the loss of attendance data. This also delays reporting to the Polres Financial Section for performance allowance disbursement. This attendance report significantly influences the allocation of performance benefits according to Regulation Number 7 of 2020 issued by the Chief of the Indonesian National Police. To address this issue, the author conducted an analysis and designed a personnel attendance information system. With the presence of this personnel attendance information system at Polsek VII Koto, it simplifies the manual attendance recording process, thereby increasing the validity of attendance data at Polsek VII Koto. Moreover, the personnel attendance information system allows the Chief of Police at VII Koto to monitor personnel attendance more effectively, especially since the Deputy Chief position is vacant. Hence, the Chief of Police needs to directly monitor personnel attendance at Polsek VII Koto. This research resulted in the design of a prototype personnel attendance information system utilizing face recognition verification, timestamps, and a mobile-based server, aiming to make the Chief of Police at VII Koto more efficient in monitoring personnel attendance through a mobile-based platform.